Gretchen the Greenhorn - Marks, Martin (More Treasures from American Film Archives, 2004)
Dorothy Gish stars as Gretchen, the daughter of Dutch immigrant Ralph Lewis. Doing her best to adjust to her strange new homeland of the USA, Gretchen falls in love with Italian-American Frank Bennett. The plot thickens when she is kidnapped by gangsters so that her father, an engraver, will be forced to make counterfeit plates. A rousing (and amusing) rescue scene caps this cinemadaptation of Bernard McConville's story Gretchen Blunders In. Curiously, the film is not mentioned in the otherwise thorough 1973 coffee-table book Lillian and Dorothy Gish. [All Movie Guide]